2007
DOI: 10.5380/ce.v12i3.10040
|View full text |Cite
|
Sign up to set email alerts
|

A Dimensão Expressiva Do Cuidado Em Domicílio: Um Despertar a Partir Da Prática Docente

Abstract: O objetivo deste texto é relatar a experiência da vivência da prática docente e o emergir da dimensão expressiva no cuidado ao ensinar o cuidado domiciliar aos alunos de um curso de graduação em enfermagem. Vivenciar a prática docente de enfermagem incitou-nos à reflexão sobre o que é enfermagem, o que é cuidado, quem é o paciente que esta sendo cuidado, como é cuidar no domicílio, bem como qual profissional queremos formar. Assim percebemos que as dimensões de cuidado instrumental e expressiva estavam present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
3

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
(7 reference statements)
0
3
0
3
Order By: Relevance
“…9 Ainda que conhecimentos instrumentais e expressivos devam estar aliados na realização do CD, nota-se que os acadê-micos, ao realizar estágio em CD, preocupam-se em demasia com a dimensão instrumental do cuidado, em detrimento da dimensão expressiva, que é um importante fator para a realização de um cuidado único e humanizado no domicílio e que deve ser despertado pelos docentes. 10 Todos esses atributos são necessários, pois o CD tem suas especificidades que começam a ser compreendidas quando os acadêmicos têm aulas teóricas e estágio na área, como demonstrado na subcategoria "compreendendo as características do cuidado domiciliar". A partir disso, passam a perceber que o domicílio é um ambiente de cuidado de domínio do paciente; nele ocorrem as relações familiares, de conflito ou alegria e seus moradores revelam o estilo de vida adotado.…”
Section: Discussionunclassified
“…9 Ainda que conhecimentos instrumentais e expressivos devam estar aliados na realização do CD, nota-se que os acadê-micos, ao realizar estágio em CD, preocupam-se em demasia com a dimensão instrumental do cuidado, em detrimento da dimensão expressiva, que é um importante fator para a realização de um cuidado único e humanizado no domicílio e que deve ser despertado pelos docentes. 10 Todos esses atributos são necessários, pois o CD tem suas especificidades que começam a ser compreendidas quando os acadêmicos têm aulas teóricas e estágio na área, como demonstrado na subcategoria "compreendendo as características do cuidado domiciliar". A partir disso, passam a perceber que o domicílio é um ambiente de cuidado de domínio do paciente; nele ocorrem as relações familiares, de conflito ou alegria e seus moradores revelam o estilo de vida adotado.…”
Section: Discussionunclassified
“…Some of them promptly organize the required material, perform the care, show their care to patients, caregivers and family members and highlight issues to be discussed; however, other students find it harder to visualize these aspects and end up waiting for teachers' instructions. 10 While relating the statements of these authors to the subcategories of the category "Expanding the knowledge related to home care", it is found that they occur to a greater or lesser extent, depending on the students' predisposition and willingness.…”
Section: Discussionmentioning
confidence: 99%
“…6:85 Thus, during the internships, teachers seek to show students the ways to care for patients, their families and caregivers and try to insert each group of students into the context in which they are working and make them aware that, despite the adversities in relation to social, environmental and clinical conditions of patients and family members, HC should be a therapeutic moment. 10 While addressing HC, the category "Coming across nuances of home care" is showed and permits the identification of the particularities in each household. It is noted that the disease of an individual affects the life of other family members and simultaneously the key role they have in the care of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…What characterizes instrumental actions is the accomplishment of technical activities aimed at attending to the biological needs expressed in the client's body, and at the physical care involving this body, with a view to planning and organizing the therapeutic environment and the equipment and material needed to accomplish technical nursing procedures (21)(22) . The instrumental actions demand empirical knowledge and technical and management skills from nurses.…”
Section: Discussionmentioning
confidence: 99%